2016
DOI: 10.1111/gcb.13499
|View full text |Cite
|
Sign up to set email alerts
|

Increasing nest predation will be insufficient to maintain polar bear body condition in the face of sea ice loss

Abstract: Climate change can influence interspecific interactions by differentially affecting species-specific phenology. In seasonal ice environments, there is evidence that polar bear predation of Arctic bird eggs is increasing because of earlier sea ice breakup, which forces polar bears into nearshore terrestrial environments where Arctic birds are nesting. Because polar bears can consume a large number of nests before becoming satiated, and because they can swim between island colonies, they could have dramatic infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 67 publications
0
34
0
Order By: Relevance
“…This study represents the first attempt to quantify seabird as prey in the diet of polar bears and has only one potentially representative avian species; therefore, we recommend further research to quantify the different seabird species and other potential onshore prey susceptible to polar bear predation and at what rates, as these pieces of evidence would suggest how onshore foraging by polar bears may impact seabird populations. Although our study has suggested that they may only represent a relatively minor component of polar bear diets, devastation of breeding colonies by polar bear predation has been reported (Dey et al, ; Iverson et al, ; Smith et al, ), and if sustained over multiple breeding seasons, creates the potential for localized reproductive failure.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…This study represents the first attempt to quantify seabird as prey in the diet of polar bears and has only one potentially representative avian species; therefore, we recommend further research to quantify the different seabird species and other potential onshore prey susceptible to polar bear predation and at what rates, as these pieces of evidence would suggest how onshore foraging by polar bears may impact seabird populations. Although our study has suggested that they may only represent a relatively minor component of polar bear diets, devastation of breeding colonies by polar bear predation has been reported (Dey et al, ; Iverson et al, ; Smith et al, ), and if sustained over multiple breeding seasons, creates the potential for localized reproductive failure.…”
Section: Discussionmentioning
confidence: 60%
“…Observations of predatory activities of individual polar bears in a small number of subpopulations have suggested substantial depredation of colonial nesting seabirds, particularly in recent years (Dey et al, ; Iverson et al, ; Smith et al, , G. Divoky, unpublished data). However, the actual contribution of this onshore resource to the diets of polar bears at the subpopulation‐level has not been previously evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The energy efficiency of egg scavenging will depend to a great extent on whether the bear is actively targeting and moving from nest to nest, using either olfactory or visual cues as did the bear eating eider eggs (appendix: 3), or if the bear is simply eating eggs from nests as they are randomly encountered (cf. Dey et al, 2017).…”
Section: Discussionmentioning
confidence: 99%